Effect of Plastic Prestraining of 25 Steel on the Diffusion Saturation of its Surface with Boron and Carbon - Filonenko, N. Yu.; Філоненко, Н. Ю.; Bereza, Olena; Береза, Олена Юріївна; Pilyaeva, S. B.; Піляєва, С. Б. (The Institute of Mathematics of the National Academy of Sciences of Ukraine, 2015)
It is shown that plastic prestraining intensifies the diffusion of carbon and boron. We obtain boron-cemented layers with homogeneous structure and improved physicochemical properties hardened with finely divided boron carbides. Показано, що пластичне попереднє напруження інтенсифікує дифузію вуглецю та бору. Одержуємо борцементовані шари з однорідною структурою та покращеними фізико-хімічними властивостями, які зміцнені тонкодисперсними карбідами бору.
Вплив попереднього пластичного напруження сталі 25 на дифузійне насичення її поверхні бором і вуглецем
Keywords: plastic prestraining; пластична попередня напруга; intensification of diffusion; інтенсифікація дифузії; boron cementation; борна цементація; Fe2 B iron boride; Fe2 B борид заліза; Fe23(CB)6 cubic boron carbide; Кубічний карбід бору Fe23(CB)6; Fe3(CB) boron cementite; Fe3(CB) борцементит